A numerical investigation of new types of bolted joints for cold-formed steel moment-resisting frame buildings. (15th April 2023) - Yin, Lingfeng; Niu, Yu; Quan, Guan; Gao, Han; Ye, Jun
Abstract: Thin-walled cold-formed steel (CFS) structures have seen an increasing application in low-to multi-story buildings. However, the immature investigation of the seismic performance of the new types of CFS joints has limited the application of CFS structures in seismic regions. This paper presents numerical investigations of the seismic performance of two types of beam-to-column CFS joints, which were proposed to be used to connect CFS members in T-, L- and cruciform joints for multi-story framed buildings. Experimental and numerical studies of the seismic performance of an additional type of gusset-place joints are also reported. As the gusset-plate joints have been well-studied by previous researchers, they are used as benchmark cases in this research. The FE models, which are set up using the commercially available software ABAQUS, are validated against test results. Good agreements between the FE modelling results and the tests are achieved. Parametric studies are carried out to investigate the factors that influence the seismic performance of the proposed CFS joints. The investigated factors include the initial stiffness, the load-bearing capacity and the ductility of the joints. Comparisons of the seismic performance are carried out between the proposed two types of joints and the gusset plate joint. Recommendations are made for the improvement of the seismic performance of the proposed joints. The results show that the initial stiffness of the proposed joints lies between 1 and 4 times EI/l . As Eurocode 3 Part 1–8 defined joints to be rigid if the stiffness is no smaller than 25 EI/l, the joints to be pinned if the stiffness is no larger than 0.5 EI/l, and the joints are semi-rigid if the stiffness is between 25 EI/l and 0.5 EI/l, the proposed joints designed in this paper can be classified within the semi-rigid classification. By changing the thickness of the components, the ductility of the proposed joints can be significantly improved. Considering the different bearing capacities of the two types of joints, it is recommended that the two joints connect the main beam and the secondary beam respectively. Highlights: New types of joints proposed for moment-resisting frames. Numerical studies conducted to investigate the structural seismic performance. Comparisons with well-studied benchmark joint. The proposed joints provided good stiffness, strength, and ductility. Recommendations to improve seismic performance of the proposed joints.